Aqua Zumba Versus Aqua Jogging: Comparative Effects on Health Parameters among Obese Middle Aged Women - Sarina, Md. Yusof (Kementerian Pendidikan Tinggi (KPT), Malaysia, 2018)
Link to publisher's homepage at http://www.mohejournal.com/index.php/mohe